Aprendizagem motora em idosos: efeitos do foco de atenção na aprendizagem de uma habilidade motora de equilíbrio - Wally, Raquel do Sacramento (2010)
The current study aims at checking the effects of focus of attention direction in the learning of a balancing motor skill in the elderly. 34 subjects will take part in the study, randomly divided into two groups, in accordance with the different types of attention focus: internal and external. The participants will be submitted to a dynamic balance task on a balancing platform, where they will have to try to maintain the platform at a horizontal position for as long as they can within each trial. The tested hypothesis is that subjects who practice with external attention focus will reach a higher learning than those who practice with an internal focus of attention, in accordance with results from previous studies (Wulf, 2007). The acquisition phase will consist of ten trials and after 24 hours; the subjects will be submitted to a retention test consisting of six trials, without any instructions related to the attention focus. Key